Confusion, clarity, cohesion, disintegration: a study of curriculum decision-making in citizenship education. - Parkin, Glenda (Curtin University, 2002)
In the last decade, the Commonwealth Government has relied increasingly on policy-induced consortia to implement its education policy initiatives. The study focused on education policy pertaining to citizenship education, and specifically on the recommendations of the Civics Expert Group's 1994 report Whereas the people...Civics and Citizenship Education. The then Commonwealth Government called for policy-induced consortia to submit applications as a means to implement the report's recommendations. As a result, the Western Australian Consortium for Citizenship Education was formed. The Consortiums submission for a grant to assist teachers to prepare curriculum materials for citizenship education was successful. The study examined the decisions made by the Consortium members in relation to the curriculum materials project.The study was informed by an examination of literature pertaining to citizenship and citizenship education, the implementation of public policy, and group and curriculum decision-making. The review of the literature concerning the constructs of 'citizen' highlighted the contested nature of citizenship. In turn, this is reflected in the debates about the nature of citizenship education. As well, the literature review revealed many models of policy implementation and group curriculum decision-making do not adequately reflect the complexities and realities of group decision-making processes. The models often ignore the socio-political dynamics of the group, particularly in a policy-induced consortium, which exists for a specific and limited purpose, where members owe allegiance to their institutions rather than the consortium and where the consortium is accountable to a government department for the management of the project.A case study approach using qualitative methods was used. These methods and approaches are most likely to capture and interpret the humanness of group decision-making. Moreover, they take into account the importance of the values each member of the Consortium brought to the group and recognise that each member constructed his/her meaning as a result of social interaction with other Consortium members.The case study focused on a detailed examination of the work of the Western Australian Consortium for Citizenship Education and especially on the sub-group of the Project Management Committee over eighteen months. The notion of 'critical decisions' was used to analyse the Consortium's decision-making. Each critical decision had significant consequences for the ongoing work of the Consortium. The nature of the Consortium's decision-making highlighted the overwhelming importance of social dynamics over curriculum decision-making.The intentions of the study were to build towards a more complete understanding of the socio-political nature of group curriculum decision-making; to contribute to theorising about the humanness of group curriculum decision-making; and to provide an informed perspective about the significance of the Commonwealth Government's intervention in education through the mechanism of policy-induced consortia.The thesis makes a contribution to the socio-political dimension of group curriculum decision-making in federations. It illustrates that curriculum policy delivery is a socio-political process focussing on interpersonal relationships rather than a rational or deliberative process based on educational outcomes.